History of Medieaval Hindu India : Volume 1: Rise of Hindu Kingdom - Vaidya, C.V., (Brill | Manohar Publishers & Distributors, 2024)
This book is the first part of the three-volume series of History of Medieaval Hindu India. It is divided into two parts. The author starts with the reign of Harsha and the kingdoms in North and Central India, which were contemporary to Harsha's reign. This volume covers the social, religious, political, civil, and military aspects from c.500-800. The book further examines the Sindh kingdoms and the expansion of the Umayyad Caliphate into the Sind, the profile of Kabul Shahis, and the Hindu kingdoms of Kashmir in greater detail. The author also covers the popular kingdoms such as Vallabhis, Chalukyas, Pallavas, Kesaris of Orissa, and other minor kingdoms throughout the Indian subcontinent before the establishment of Delhi Sultanates.